Kurikulum Merdeka Sebagai Jawaban Tantangan Global - Eny Junyanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Curriculum is one of the important aspects in meeting global demands in education. In the context of globalization, there is an increasing demand for relevant and effective curricula. This article explores how the curriculum meets the needs of the world, taking into account various factors, including technological advances, the needs of the global labor market, and the universal values and skills needed in today's global society. whether we can respond to it. Through this research, it is hoped that an approach can be found that can guide curriculum development in responding to global needs, so as to create a generation that is able to compete and contribute on a global scale.